One Step Forward, Two Steps Backward? Does E-Government Make Governments in Developing Countries More Transparent and Accountable? - Lemieux, Victoria L. (World Bank, Washington, DC, 2016)
Many countries are in the process of transitioning from primarily paper-‐based administrative systems to digital systems through the application of information and communication technology (ICTs) as part of e-‐Government initiatives. Though much has been written about the positive power of technology and information to support greater transparency and accountability and, by extension, development, this paper discusses literature relating to the unintended consequences and downside risks for transparency and accountability associated with the way recorded information is produced and managed in digitally enabled developing country public sector contexts. The implications of these risks for implementation of right to information laws is discussed, and a call is made for further research and greater attention to the effects of ICT use in the public sector, especially in regard to effects upon the operation of transparency and accountability mechanisms.